Performance of Series Connected GaAs Photovoltaic Converters under Multimode Optical Fiber Illumination. (18th December 2014) - Shan, Tiqiang; Qi, Xinglin
Abstract : In many military and industrial applications, GaAs photovoltaic (PV) converters are connected in series in order to generate the required voltage compatible with most common electronics. Multimode optical fibers are usually used to carry high-intensity laser and illuminate the series connected GaAs PV converters in real time. However, multimode optical fiber illumination has a speckled intensity pattern. The series connected PV array is extremely sensitive to nonuniform illumination; its performance is limited severely by the converter that is illuminated the least. This paper quantifies the effects of multimode optical fiber illumination on the performance of series connected GaAs PV converters, analyzes the loss mechanisms due to speckles, and discusses the maximum illumination efficiency. In order to describe the illumination dependent behavior detailedly, modeling of the series connected PV array is accomplished based on the equivalent circuit for PV cells. Finally, a series of experiments are carried out to demonstrate the theory analysis.